Food Prices Policy: Relational Implementation of Fiqh Muamalah and Islamic Economics: Kebijakan Harga Pangan: Implementasi Hubungan Fiqh Muamalah dan Ekonomi Islam - Zakiyyul Fuad (Islamic Economics Department, Faculty of Islamic Economics and Business, Sunan Ampel State Islamic University, Surabaya Indonesia, 2022)
There are fundamental differences between Islamic economics and Fiqh Muâ€˜Ämalah, as well as the relationship between the two, according to Anas Zarqa and Monzer Khaf. However, according to Qadri Azizi, Islamic economics and Fiqh Muâ€˜Ämalah are not different because there is no difference in terms of material objects. This study aims to understand the food price policy by the government as a relational implementation of Fiqh Muâ€˜Ämalah and Islamic economics by analyzing the epistemology of Islamic economics between economics and Fiqh Muâ€˜Ämalah, and also to understand the relation between Fiqh Muâ€˜Ämalah and Islamic economics in food price policy by the government as a strategic study of the economy. This study is qualitative descriptive, using a content analysis tool and literature study. The results of this study are 1) There are fundamental differences between economics and Fiqh Muâ€˜Ämalah in the epistemological aspect, which creates a scientific discipline that combines the two into Islamic Economics. 2) Fiqh Muâ€˜Ämalah as a normative study sourced from the Alquran and hadith functions as a basis in economic cases through observation and description of phenomena. Therefore, without a touch of values and sharia norms, economics remains value-free. In terms of food price policy, factors such as economic conditions, consumer behavior, and policy implications will be a reference in normative-strategic studies for Islamic economists to sort out and determine rules that are more relevant and have greater maá¹£laá¸¥ah.